Distinct expression of NEAT1 isoforms in Parkinson’s disease models suggests different roles of the variants during the disease course - Boros, Fanni Annamária; Horváth, Orsolya; Maszlag-Török, Rita; Baranyi, Mária; Nánási, Nikolett; Oláh-Németh, Orsolya; Sperlágh, Beáta; Vécsei, László; Klivényi, Péter (Scientific Reports, 2025)
Parkinson’s disease (PD) is the second most common neurodegenerative disease worldwide. Recently long non-coding RNAs (lncRNAs) have emerged as possible molecular hubs in the diverse pathomechanisms of the disease. Among them, NEAT1 gained particular interest due to findings suggesting both protective and deleterious effects of this lncRNA in PD models.The aim of this study was to clarify some of the contradictions among data that appeared in recent publications concerning NEAT1 effects. For this, we determined whether pharmacological increase of NEAT1 levels worsened the detrimental effect of MPP + in the SH-SY5Y cell model, and whether the levels of the short and long isoform of the lncRNA changed differently upon short and extended MPTP treatment in an MPTP-induced mouse model of PD. Our findings suggest differential expression of NEAT1/Neat1 isoforms in MPP + /MPTP-induced PD models, which is in accord with the proposed role of the lncRNA in the general stress response. We propose that first an early up-regulation of Neat1_2 is dominant. The level of Neat1_2 then decreases as pathology progresses, resulting in a shift in the ratio of the two isoforms towards a higher level of Neat1_1 accompanied by damage of the central nervous system.
CRIS-Team Scopus Importer:2025-05-02
Keywords: lncRNA; MAO; MPTP; NEAT1; Neat1; Neurodegeneration; Parkinson’s disease